2018
DOI: 10.1007/s10340-018-0951-7
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of climate and agroenvironmental factors on wireworm damage risk in maize crops

Abstract: A large-scale survey was carried out in 336 French fields to investigate the influence of soil characteristics, climate conditions, the presence of wireworms and the identity of predominant species, agricultural practices, field history and local landscape features on the damage caused by wireworms in maize. Boosted regression trees, a statistical model originating from the field of machine learning, were fitted to survey data and then used to hierarchize and weigh the relative influence of a large set of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
(90 reference statements)
0
20
0
1
Order By: Relevance
“…The larvae of the Elateridae are (known as ‘wireworms’) live in soil and/or under bark and feed and process decaying soil organic matter 56 . The wireworm larval stage can span from 2 to 6 years, and in some cases even 10 years 56 58 . During this larval period, wireworms specifically feed underground making them persistent residents of soil for some time.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae of the Elateridae are (known as ‘wireworms’) live in soil and/or under bark and feed and process decaying soil organic matter 56 . The wireworm larval stage can span from 2 to 6 years, and in some cases even 10 years 56 58 . During this larval period, wireworms specifically feed underground making them persistent residents of soil for some time.…”
Section: Discussionmentioning
confidence: 99%
“…We applied a statistical method from the field of machine learning, namely, BRT 34,35 , to build a stochastic, nonlinear regression model from our dataset. This method is attracting increasing interest in ecology and epidemiology 3640 . BRT combines the advantages of regression trees (capable of handling qualitative and quantitative predictors and accommodating missing data, and prior information or data transformation is not needed) and boosting (improves prediction accuracy by combining many simple models) 36 .…”
Section: Methodsmentioning
confidence: 99%
“…They also found that soil pH was a strong predictor for the abundance of A. obscurus and A. ustulatus. Based on a large-scale survey carried out in 336 maize fields over three years in France, Poggi et al [25] concluded that soil characteristics had a prominent influence on wireworm damage risk, ranking them third after the presence of wireworms and climatic variables, with both pH and organic-matter content also being major factors. The effects of soil texture, drainage, and other factors can be found in the literature (see for example Furlan et al [23]).…”
Section: Risk Factorsmentioning
confidence: 99%